Analysis of the Carrying Capacity of Rice Commodity Agricultural Land Management in North Kolaka Regency - Ainuddin, Ainuddin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Agriculture is the main sector that supports the rural economy in North Kolaka Regency, with rice as a staple food commodity for the community. However, population growth, climate change, and the conversion of rice fields are serious challenges to the availability of local rice food. This study aims to analyze the availability of rice food, the need for rice fields, and the carrying capacity status of agricultural land in North Kolaka Regency, as well as projecting the needs of the next five years. The research method uses a descriptive quantitative approach with secondary data from BPS, Bappeda, and the Food Crops and Horticulture Service, as well as primary observations for field verification. The analysis included the calculation of rice food availability based on land productivity, food needs based on per capita consumption, and the Land Carrying Capacity Index (IDDL) with the Odum, Howard, and Issard formula. The results of the study showed that the average availability of rice food reached Â±7,000 tons/year, with an uneven distribution between sub-districts. Some areas such as Ranteangin and Batu Putih are in surplus conditions, while other sub-districts tend to have deficits or do not have significant production. The IDDL shows a downward trend due to a reduction in harvest area of about 2.1% in the last five years, while food needs increase as the population grows. Projections over the next five years show that the risk of deficit is even greater if there is no policy intervention. These findings confirm the need for strategies to strengthen regional food security through agricultural intensification (increasing planting index, superior seeds, irrigation efficiency), sustainable rice field protection (LP2B), and diversifying local food. The results of the research are expected to be a reference for local governments in spatial planning, land conversion control, and sustainable food security policy formulation.